2012
DOI: 10.1149/2.032207jes
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Electrochemical Properties of 1-Ethyl-3-Methylimidazolium Tris(pentafluoroethyl)trifluorophosphate and 1-Ethyl-3-Methylimidazolium Tetracyanoborate

Abstract: The physicochemical (e.g., density, viscosity, ionic conductivity, and self-diffusion coefficient) and electrochemical (e.g., electrochemical window and electric double-layer capacitor performance) properties of two new types of room-temperature ionic liquids, 1-ethyl-3-methylimidazolium tris(pentafluoroethyl)trifluorophosphate (EMIm-FAP) and 1-ethyl-3-methylimidazolium tetracyanoborate (EMIm-TCB), were investigated and compared. EMIm-FAP showed a wider electrochemical window with a carbon working electrode co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 22 publications
8
36
4
Order By: Relevance
“…For this IL only limited information is available so far. They are in excellent agreement with the η(T) values published 58 for η(T) in the temperature range of (283.15 to 353.15) K exhibits relative deviations of only −0.034 ≤ δ ≤ 0.01 from the present fit but the dependence of η on temperature is somewhat smaller. They are in excellent agreement with the η(T) values published 58 for η(T) in the temperature range of (283.15 to 353.15) K exhibits relative deviations of only −0.034 ≤ δ ≤ 0.01 from the present fit but the dependence of η on temperature is somewhat smaller.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For this IL only limited information is available so far. They are in excellent agreement with the η(T) values published 58 for η(T) in the temperature range of (283.15 to 353.15) K exhibits relative deviations of only −0.034 ≤ δ ≤ 0.01 from the present fit but the dependence of η on temperature is somewhat smaller. They are in excellent agreement with the η(T) values published 58 for η(T) in the temperature range of (283.15 to 353.15) K exhibits relative deviations of only −0.034 ≤ δ ≤ 0.01 from the present fit but the dependence of η on temperature is somewhat smaller.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…Ignatev et al 66 reported a single κ value, determined at 293.15 K with a commercial conductometer of 0.5% relative standard uncertainty, which is 0.9 % below the present fit ( Figure S12). Note that a similar discrepancy also exists for η, where the experimental point (43 mPa·s) of ref 58. Only a single numerical value at 303.15 K was published, together with the parameters of a VFT fit to their data.…”
Section: ■ Results and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our value for D S+ is 0.87 7 . However, the cation−cation VCC, f ++ , calculated from the self-diffusion data of Seki et al 34 and the conductivities of Nazet et al 44 are positive, which is an unphysical result, and another reason for believing these selfdiffusion data are too low.…”
Section: Transport Properties Of [Emim][chmentioning
confidence: 92%
“…Ionic liquids based on the FAP anion reveal an excellent electrochemical (Fig.3) [5,[7][8][9][10] and thermal stability [5,11,12]. They are less viscous than corresponding ionic liquids with the [PF 6 ] -anion [5,13,14].…”
Section: Tris(perfluoroalkyl)phosphate (Fap) Ionic Liquidsmentioning
confidence: 99%